Uji Validasi Pegembangan LKS (Lembar Kerja Siswa) Biologi SMA Berbasis Problem Based Learning pada Materi Perubahan Lingkungan untuk meningkatkan kemampuan berfikir kritis - Henny Hadiyatul Maulia; Tabitha Sri Hartati Wulandari (Universitas Sebelas Maret, 2018)
This study aims to determine the validity of student workbooks based on problem based learning on environmental change materials to improve the ability to think critically in high school. This research is research development (Research and The develop-ment) is a 4-D model. This model consists of 4 development stages including Defining, Designing, Development, and Spreading. But in this study only until the development stage is up to the stage of validity. The research was conducted in August 2018. This research was conducted in MA Syiar Islam Maibit Rengel. The data collected in this study is the data of LKS validity test results. The instrument used to collect data in this study is a questionnaire. The data in this study were analyzed by using descriptive statistics in the form of percentage. The result of the validity of the media expert is 81.5 and the material expertity validity is 82.5 with very valid criteria. Thus it is concluded that the developed LKS can be used to improve critical thinking.